Epigenome-wide association study reveals methylation pathways associated with childhood allergic sensitization. Issue 5 (4th May 2019) - Peng, Cheng; Van Meel, Evelien R.; Cardenas, Andres; Rifas-Shiman, Sheryl L.; Sonawane, Abhijeet R.; Glass, Kimberly R.; Gold, Diane R.; Platts-Mills, Thomas A.; Lin, Xihong; Oken, Emily; Hivert, Marie-France; Baccarelli, Andrea A.; et al.
ABSTRACT: Epigenetic mechanisms integrate both genetic variability and environmental exposures. However, comprehensive epigenome-wide analysis has not been performed across major childhood allergic phenotypes. We examined the association of epigenome-wide DNA methylation in mid-childhood peripheral blood (Illumina HumanMethyl450K) with mid-childhood atopic sensitization, environmental/inhalant and food allergen sensitization in 739 children in two birth cohorts (Project Viva–Boston, and the Generation R Study–Rotterdam). We performed covariate-adjusted epigenome-wide association meta-analysis and employed pathway and regional analyses of results. Seven-hundred and five methylation sites (505 genes) were significantly cross-sectionally associated with mid-childhood atopic sensitization, 1411 (905 genes) for environmental and 45 (36 genes) for food allergen sensitization (FDR<0.05). We observed differential methylation across multiple genes for all three phenotypes, including genes implicated previously in innate immunity ( DICER1 ), eosinophilic esophagitis and sinusitis ( SIGLEC8 ), the atopic march ( AP5B1 ) and asthma ( EPX, IL4, IL5RA, PRG2, SIGLEC8, CLU ). In addition, most of the associated methylation marks for all three phenotypes occur in putative transcription factor binding motifs. Pathway analysis identified multiple methylation sites associated with atopic sensitization and environmental allergen sensitization located in/near genes involved in asthma, mTOR signaling, and inositol phosphate metabolism. We identified multiple differentially methylated regions associated with atopic sensitization (8 regions) and environmental allergen sensitization (26 regions). A number of nominally significant methylation sites in the cord blood analysis were epigenome-wide significant in the mid-childhood analysis, and we observed significant methylation – time interactions among a subset of sites examined. Our findings provide insights into epigenetic regulatory pathways as markers of childhood allergic sensitization.